2017
DOI: 10.1038/s41387-017-0007-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of omega-3 supplements and fresh fish on lipid profile: a randomized, open-labeled trial

Abstract: BackgroundDietary fish is a rich source of Omega-3 poly-unsaturated fatty acids (PUFAs). These compounds may have protective effect against cardiovascular events possibly by modifying lipid profiles. Consequently, fish oil supplements are produced commercially to complement low fish intake. It is not clear if both interventions have similar effects. The aim of this trial was to compare the anti-hyperlipidemic effect of omega3 fatty acid supplements with fresh fish.MethodA total of 106 patients with hyperlipide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 37 publications
1
52
1
1
Order By: Relevance
“…While research has shown how different sources of omega‐3 fatty acids affect lipid profile and cytokine gene expression, there is a lack of research to determine the mechanisms whereby different sources of omega‐3 fatty acids affect blood pressure . It is suggested that further research is necessary to adequately study this topic to determine how the dietary source of omega‐3 fatty acids plays a role in lowering blood pressure and differentially affecting systolic and diastolic blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…While research has shown how different sources of omega‐3 fatty acids affect lipid profile and cytokine gene expression, there is a lack of research to determine the mechanisms whereby different sources of omega‐3 fatty acids affect blood pressure . It is suggested that further research is necessary to adequately study this topic to determine how the dietary source of omega‐3 fatty acids plays a role in lowering blood pressure and differentially affecting systolic and diastolic blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary, data of Zibaeenezhad et al (2017) indicated that, total cholesterol, non-HDL cholesterol, triglycerides (TG) levels, and Castelli I index were reduced significantly, while HDL level increased significantly following the feeding on fish oil or fresh fish in human. Meanwhile LDL level was increased in fish oil group.…”
Section: Lipid Profile In Blood Serummentioning
confidence: 92%
“…Also, Ashraf et al (2017) found insignificant effect of different dietary sources (olive oil, black seed oil and flaxseed oil) on serum cholesterol, triglycerides and HDL. Moreover, Zibaeenezhad et al (2017) observed that Castelli II index did not change following the feeding on fish oil or fresh fish in human.…”
Section: Lipid Profile In Blood Serummentioning
confidence: 97%
See 1 more Smart Citation
“…45 So even though there can be significant differences among encapsulated omega-3 formulations, 52 it is not unreasonable to assume that equivalent doses of EPA þ DHAdfrom whatever sourcedshould have similar effects on risk of CVD. 53…”
Section: Omega-3 Recommendationsmentioning
confidence: 99%